Pemanfaatan Koleksi Kitab Kuning Santri Putri di Perpustakaan Pondok Pesantren Darul Arafah Raya Deli Serdang - Siregar, Fauziyah; Azhar, Anang Anas; Yusniah, Yusniah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research explores the Utilization of Yellow Book Collections by Female Students at the Library of Darul Arafah Raya Islamic Boarding School in Deli Serdang. The aim of this study is to determine whether the yellow book collections for female students in the library of Darul Arafah Raya Islamic boarding school have been utilized and to identify the obstacles experienced by female students in utilizing the yellow book collections available in the library of Darul Arafah Raya Islamic boarding school. This research is descriptive in nature, employing a qualitative approach with data collection techniques including observation, interviews, and documentation. The findings of this study indicate that the utilization of yellow book collections by female students in the library of Darul Arafah Raya Islamic boarding school has not been fully exploited, as the female students encounter difficulties in understanding and utilizing the yellow books due to the absence of diacritical marks (fathah, kasrah, dhammah, sukun). Additionally, their everyday vocabulary (mufhrodat) is still lacking, and their proficiency in studying nahwu and sharaf is weak. The obstacles to the utilization of yellow book collections for female students at the library of Darul Arafah Raya Islamic boarding school include the absence of diacritical marks (fathah, kasrah, dhammah, sukun) in the yellow books, which makes it difficult for female students to comprehend them. Furthermore, the difficulty in interpreting the yellow books is due to the lack of everyday vocabulary, the weakness in Arabic language proficiency among female students, the absence of specific schedules for learning yellow books, and the lack of communication between female students and teachers in yellow book learning.